Implikasi Perjanjian TRIMs terhadap Perekonomian Domestik di Abad 21: Studi Pengembangan Hukum - Satrih Hasyim; La Ode Husen; Nasrullah Nasrullah (CV. Social Politic Genius (SIGn), 2022)
This study aims to analyze the implications of the TRIMs agreement for Indonesia. It discusses the exceptions to the TRIMs agreement, the utilization of transition periods, as well as the efforts of the Government to increase the investment value. This normative legal study uses statute, sociological, and comparative approaches with a literature study technique. The study results a show that Indonesia implements the TRIMs agreement, considering the exceptions and transition period. The Government’s efforts to increase investment include clear legal protection, improvement of human resources, a conducive investment environment, digital technology, innovative approach, and simplifying the investment process. Therefore, it is recommended that the Government strengthens investment regulations and policies that consider the development of society and the business world and increases investment in education and digital technology. The community must also actively participate in helping to increase investment by creating a conducive investment environment. With reasonable efforts and cooperation, investment in Indonesia is expected to increase and positively impact Indonesia’s economic growth in the 21st century.